Health and social burdens of TB-HIV co-infection in Indonesian risk populations - Nur Indah Chairunnisa; Dwi Sarwani Sri Rejeki; Siwi Pramatama Mars Wijayanti (Institute of Computer Science (IOCS), 2026)
This systematic literature review aims to examine the health and social burdens of TB-HIV co-infection among at-risk populations in Indonesia. The review analyzed four quantitative primary studies published between 2021 and 2024, including three from Indonesia and one from Ethiopia as a comparative reference. Literature was identified from electronic databases using defined inclusion criteria and screened through PRISMA guidelines. Data were extracted on sample characteristics, quantitative instruments, and statistical findings relevant to TB-HIV prevalence, risk factors, treatment challenges, and public health interventions. Results showed that TB-HIV co-infection poses significant burdens, especially among populations with low socio-economic status and limited access to healthcare. Key challenges include poor treatment adherence, stigma, psychological distress, and fragmented health services. Although some interventions have been implemented, they remain inconsistent and unequally distributed. This review highlights the need for integrated, community-based, and multi-sectoral approaches to address TB-HIV co-infection in Indonesia’s vulnerable populations effectively.